The Inter-Relationship of Platelets with Interleukin-1β-Mediated Inflammation in Humans - Tunjungputri, Rahajeng N.; Li, Yang; de Groot, Philip G.; Dinarello, Charles A.; Smeekens, Sanne P.; Jaeger, Martin; Doppenberg-Oosting, Marije; Cruijsen, Milou; Lemmers, Heidi; Toenhake-Dijkstra, Helga; Aguirre-Gamboa, Raul; Kumar, Vinod; Wijmenga, Cisca; Joosten, Leo A. B.; Netea, Mihai G.; van der Ven, Andre; de Mast, Quirijn (Thrombosis and Haemostasis, 2018)
Background Inflammation and coagulation are key processes in cardiovascular diseases (CVDs). The Canakinumab Anti-inflammatory Thrombosis Outcome Study trial affirmed the importance of inflammation in CVD by showing that inhibition of the interleukin (IL)-1β pathway prevents recurrent CVD. A bi-directional relationship exists between inflammation and coagulation, but the precise interaction of platelets and IL-1β-mediated inflammation is incompletely understood. We aimed to determine the inter-relationship between platelets and inflammation—and especially IL-1β—in a cohort of healthy volunteers.Methods We used data from the 500-Human Functional Genomics cohort, which consists of approximately 500 Caucasian, healthy individuals. We determined associations of plasma levels of IL-1β and other inflammatory proteins with platelet number and reactivity, the association of platelet reactivity with ex vivo cytokine production as well as the impact of genetic variations through a genome-wide association study (GWAS).Results Platelets were associated with IL-1β on different levels. First, platelet number was positively associated with plasma IL-1β concentrations (p = 8.9 × 10−9) and inversely with concentrations of α-1-anti-trypsin (p = 1.04 × 10−18), which is a known antagonist of IL-1β. Second, platelet degranulation capacity, as determined by agonist-induced P-selectin expression, was associated with ex vivo IL-1β and IL-6 production. Third, several platelet single-nucleotide polymorphisms (SNPs) were associated with cytokine production and there was a significant platelet SNP enrichment in specific biological important pathways. Finally, platelet SNPs were enriched among SNPs earlier identified in GWAS studies in blood-related diseases and immune-mediated diseases.Conclusion This comprehensive assessment of factors associated with platelet number and reactivity reinforces the important inter-relationship of platelets and IL-1β-mediated inflammation.
Keywords: platelet immunology; inflammation; infectious diseases; cytokines; platelet physiology